Assessment of environmental correlates of physical activity: development of a European questionnaire. - Spittaels, H; Foster, C; Oppert, J; Rutter, H; Oja, P; Sjöström, M; De Bourdeaudhuij, I (2009)
BACKGROUND: Research on the influence of the physical environment on physical activity is rapidly expanding and different measures of environmental perceptions have been developed, mostly in the US and Australia. The purpose of this paper is to (i) provide a literature review of measures of environmental perceptions recently used in European studies and (ii) develop a questionnaire for population monitoring purposes in the European countries. METHODS: This study was done within the framework of the EU-funded project 'Instruments for Assessing Levels of Physical Activity and Fitness (ALPHA)', which aims to propose standardised instruments for physical activity and fitness monitoring across Europe. Quantitative studies published from 1990 up to November 2007 were systematically searched in Pubmed, Web of Science, TRIS and Geobase. In addition a survey was conducted among members of the European network for the promotion of Health-Enhancing Physical Activity (HEPA Europe) and European members of the International Physical Activity and Environment Network (IPEN) to identify published or ongoing studies. Studies were included if they were conducted among European general adult population (18+y) and used a questionnaire to assess perceptions of the physical environment. A consensus meeting with an international expert group was organised to discuss the development of a European environmental questionnaire. RESULTS: The literature search resulted in 23 European studies, 15 published and 8 unpublished. In these studies, 13 different environmental questionnaires were used. Most of these studies used adapted versions of questionnaires that were developed outside Europe and that focused only on the walkability construct: The Neighborhood Environment Walkability Scale (NEWS), the abbreviated version of the NEWS (ANEWS) and the Neighborhood Quality of Life Study (NQLS) questionnaire have been most commonly used. Based on the results of the literature review and the output of the meeting with international experts, a European environmental questionnaire with 49 items was developed. CONCLUSION: There is need for a greater degree of standardization in instruments/methods used to assess environmental correlates of physical activity, taking into account the European-specific situation. A first step in this process is taken by the development of a European environmental questionnaire.